2022
DOI: 10.58490/ctump.2022i4.467
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular Intervention for Acute Ischemic Stroke at Can Tho University of Medicine and Pharmacy Hospital

Abstract: Introduction: Acute cerebral ischemic stroke is a life-threatening emergency with high incidence of mortality and morbidity. Endovascular revascularization has been increasingly used as one of the treatment options. In this article, we report our outcomes of endovascular intervention for the treatment of ischemic stroke and highlight some technical experiences. Materials and methods: A cross-sectional descriptive study was conducted on all cerebral ischemic stroke patients who came to Can Tho University of Med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 5 publications
0
0
1
Order By: Relevance
“…This trend was also observed in specific research populations, such as inpatients with cardiovascular diseases aged 35 years and older, in the study of Sagita 14 , which reduced both the number and types of DRPs; however, the occurrence of DRPs at each stage was independent (p-value>0.05). This result differs from similar studies (p-value<0.01) and differences in intervention forms between studies on specific patient populations [14][15][16] .…”
Section: Discussioncontrasting
confidence: 97%
“…This trend was also observed in specific research populations, such as inpatients with cardiovascular diseases aged 35 years and older, in the study of Sagita 14 , which reduced both the number and types of DRPs; however, the occurrence of DRPs at each stage was independent (p-value>0.05). This result differs from similar studies (p-value<0.01) and differences in intervention forms between studies on specific patient populations [14][15][16] .…”
Section: Discussioncontrasting
confidence: 97%
“…The onset circumstances by blending or rotating accounted for the highest prevalence (45%), which was similar to the Tran and colleagues (48.1%;Tran & Le, 2018) and Nguyen and team (51.43%;Nguyen, 2014) Sensory disorder (98% foot numbness, 34% sensation reduced) and reflex disorder (40% patellar reflex reduction, 50% Achilles reflex reduction) (Table 2) were similar to some studies such as 100% sensory disorder, and 58.5% reflex disorders (Tran & Le, 2018), 65.11% sensory disorder and 43.33% reflex disorders (Duong, 2015), and 72% sensory disorder (Lewis et al, 1987).…”
Section: Possible Explanations and Comparisons With Other Studiessupporting
confidence: 83%
“…Muscle atrophy in our study (18%) was lower than as reported by Nguyen and the team's study (48.7%) (Nguyen, 2014) Lewis et al, 1987). This difference was because of the distinctive living habits and occupations between populations.…”
Section: Possible Explanations and Comparisons With Other Studiescontrasting
confidence: 78%
See 2 more Smart Citations